The Impact of Javanese Dance on Improving Rhythmic Skills and Critical Thinking - Mulyaningsih, Farida; Susanto, Ermawan; Sukoco, Pamuji; Suryobroto, Agus S.; Ilmah, Nur Khozanah (Physical Education Theory and Methodology, 2023)
Study purpose. The low rhythmic skills of students are caused by the complexity of rhythmic movements. This study aims to determine the impact of Javanese dance on rhythmic skills and critical thinking. Materials and methods. The study used a one group pretest-posttest experimental design. Fourth grade students of 66 people were used as research subjects who were taken through cluster random sampling. Rhythmic skill data collection was using Rhythmic Test and critical thinking data collection was using a questionnaire. Data analysis was used to determine the impact of Javanese dance using paired samples t-tests, while proving the difference in impact was using independent samples t-tests. Results. The results show that the paired samples t-test in rhythmic skills is known to have t-test > t-table or 7.540 >1.980, p = 0.00. In critical thinking t-test > t-table or 4.631 > 1.980, p = 0.00. That is, there is an impact of Javanese dance on improving students’ rhythmic skills and critical thinking (t = 6.575, p = 0.00 < 0.005). Conclusions. The applied Javanese dance has an impact on improving rhythmic skills (psychomotor aspects) and critical thinking (cognitive aspects).